Spatiotemporal hydrological analysis of streamflows and groundwater recharge for sustainable water management in Prince Edward Island, Canada. Issue 2 (19th November 2021) - Bhatti, Ahmad Zeeshan; Farooque, Aitazaz Ahsan; Krouglicof, Nicholas; Peters, Wayne; Acharya, Bishnu; Li, Qing; Ahsan, Muhammad Sheraz
Abstract: Prince Edward Island (PEI), Canada, entirely depends on groundwater for freshwater supplies, which also highly feeds streamflows. In a few watersheds, pumping has had disturbed steady‐state conditions and reduced streamflows. Spatiotemporal hydrological analysis of streamflows and recharges was performed in its scattered watersheds. Mill, Wilmot, West, Winter, and Bear River watersheds were modeled by the Soil and Water Assessment Tool (SWAT) under the shallow water‐table conditions, besides other analyses. The model was calibrated against 120 observed mean monthly flows (1995–2004) and validated for another 120 observations (2005–2014), with Nash–Sutcliffe efficiency (NSE) as the major performance assessment parameter. The model accurately simulated mean monthly flows for all watersheds during 1995–2014, except Winter River watershed (NSE = 0.02–0.33), wherein it overpredicted by 31%–52% and 5–12% in Wilmot River (NSE = 0.28–0.64). Streamflows were found highly dependent on groundwater; therefore, pumpings of 6.92 and 0.73 million cubic meters (MCM)/year caused the overpredictions in Winter and Wilmot watersheds, as SWAT cannot account pumping. In the rest three watersheds with negligible pumping, 4%–18% underprediction was due to multisite calibration. Spatially, streamflows randomly varied between 555 and 811 mm/year across watersheds, whereas thick and highly permeable sandstone produced higher recharges, the maximum 600 mm/year in the eastern forest‐dominated Bear River watershed, lesser in western 330 mm/year, and moderate 450 mm/year in central watersheds. Temporally, March–May are the months of highest streamflows, whereas recharge is maximum during April–July. The succession trend justified strong surface water–groundwater interactions. Existing Water Extraction Permitting Policy ensures sustainability at the island scale. It sets pumping limit at 20% of recharge, that is, 0.48 km 3 /year altogether, against the present pumping of 0.04 km 3 /year, yet a few watersheds are somewhat water‐stressed due to population and pumping concentration. Expansion of streamflow and groundwater monitoring, promoting population and pumping in rural areas, and more scrutiny for further pumping permits in water‐stressed watersheds are quite important for sustainable water management in PEI. 摘要: 加拿大爱德华王子岛(PEI)完全依靠地下水进行饮用水供应, 地下水在很大程度上为径流量作贡献。在一部分流域, 抽水已扰乱了稳定状态, 减少了径流量。对该岛各分散流域的径流量和地下水补给进行了时空水文分析。在浅地下水位的条件下对Mill、Wilmot、West、Winter、和 Bear流域进行了SWAT建模, 并进行了其他分析。通过120次观察的平均每月径流量(1995‐2004年)进行模型校准；并通过另外120次观察(2005‐2014年)进行模型验证, 纳什效率系数(NSE)作为主要的表现评估参数。模型精确模拟了1995‐2014年间所有流域的平均每月径流量, Winter流域和Wilmot流域除外, 前者的径流量被过高预测了31%‐52%(NSE = 0.02‐0.33), 后者的径流量被过高预测了5%‐12%(NSE = 0.28‐0.64)。分析发现, 径流量高度取决于地下水；因此, 每年6.92和0.73百万立方米(MCM)的抽水量导致Winter 和Wilmot流域的预测值过高, 因为SWAT无法分析抽水量。其余三个流域的抽水量可忽略不计, 4%‐18%的过低预测值归因于多处选址校准。从空间上看, 在厚且高度可渗透的沙石(提供更高的地下水补给)流域, 径流量随机出现在每年555‐811毫米之间；在东部森林区Bear流域, 最高径流量达到每年600毫米；西部流域径流量较少, 每年最大值为330毫米；中部流域径流量适中, 每年最大值为450毫米。从时间上看, 径流量最大的月份为三月到五月, 地下水补给最大值出现于四月至七月。交替趋势证明了地表水‐地下水的强烈相互作用。现有的采水许可政策(Water Extraction Permitting Policy)确保该岛的可持续性。该政策将抽水量限制在20%的地下水补给, 即每年0.48立方千米, 相比之下, 当前的抽水量为每年0.04 立方千米, 不过, 少部分流域在一程度上缺水, 这归因于人口和抽水集中度。对PEI可持续水管理而言尤为重要的是, 扩大径流量和地下水监测, 推动在农村地区进行抽水和人口迁移、以及对缺水流域的进一步抽水许可进行更多的监督。 Resumen: La Isla del Príncipe Eduardo (PEI), Canadá, depende completamente del agua subterránea para el suministro de agua dulce, que también alimenta en gran medida los flujos de los arroyos. En algunas cuencas hidrográficas, el bombeo ha alterado las condiciones de estado estacionario y ha reducido los caudales. Se realizó un análisis hidrológico espacio‐temporal de caudales y recargas en sus cuencas dispersas. Las cuencas de los ríos Mill, Wilmot, West, Winter y Bear River fueron modeladas por SWAT en las condiciones de las aguas poco profundas, además de otros análisis. El modelo se calibró contra 120 caudales medios mensuales observados (1995‐2004); y validado para otras 120 observaciones (2005‐2014), con NSE como el principal parámetro de evaluación del desempeño. El modelo simuló con precisión los caudales mensuales medios para todas las cuencas hidrográficas durante 1995‐2014, excepto la cuenca hidrográfica del río Winter (NSE = 0.02‐0.33), en donde pronosticó entre un 31‐52% y un 5‐12% en el río Wilmot (NSE = 0.28‐0.64 ). Se encontró que los flujos de arroyos dependían en gran medida del agua subterránea; por lo tanto, los bombeos de 6, 92 y 0, 73 millones de metros cúbicos (MCM) / año causaron las predicciones excesivas en las cuencas hidrográficas de Winter y Wilmot, ya que SWAT no puede contabilizar el bombeo. En las 3 cuencas hidrográficas restantes con bombeo insignificante, la predicción insuficiente del 4‐18% se debió a la calibración en varios sitios. Espacialmente, los caudales variaron aleatoriamente entre 555‐811 mm / año a través de las cuencas hidrográficas, mientras que la arenisca gruesa y altamente permeable produjo recargas más altas, el máximo 600 mm / año en la cuenca del río Bear, dominada por los bosques del este, y menor en el oeste 330 mm / año, y moderado 450 mm / año en las cuencas centrales. Temporalmente, marzo‐mayo son los meses de mayores caudales, mientras que la recarga es máxima durante abril‐julio. La tendencia a la sucesión justificó fuertes interacciones entre aguas superficiales y subterráneas. La política de permisos de extracción de agua existente garantiza la sostenibilidad a escala de la isla. Establece el límite de bombeo en el 20% de la recarga, es decir, 0, 48 km3 / año en total, frente al bombeo actual de 0, 04 km3 / año, sin embargo, algunas cuencas hidrográficas sufren de estrés hídrico debido a la población y la concentración de bombeo. La expansión del monitoreo del flujo de los arroyos y las aguas subterráneas, la promoción de la población y el bombeo en áreas rurales, y un mayor escrutinio para obtener más permisos de bombeo en cuencas hidrográficas con estrés hídrico, son bastante importantes para la gestión sostenible del agua en PEI.